Application of the Theory of Planned Behavior to Identify Nursing Student's Intention to be a Bystander Cardiopulmonary Resuscitation - Suis Galischa Wati; Titin Andri Wihastuti; Tina Handayani Nasution (NurseLine Journal, 2021)
Background: Theory of Planned Behavior (TPB) is a social pshycological theory which explained that someone's tendency to behave is affected by their intention. This theory often used to predict behavioral intention in health workers by measuring some aspects such as attitude, subjective norm and self efficacy. As a prospective health worker who equipped with knowledge and skills about Cardiopulmonary Resuscitation (CPR) during education phase, nursing students are expected to have a good intentions to become bystander CPR in Out of Hospital Cardiac Arrest (OHCA). Aims: This study intends to apply TPB in identifying factors that influence nursing student’s intention to perform bystander CPR. Methods: This was a quantitative study with cross-sectional approach. The research population were undergraduate nursing student in Malang, while the 108 samples were taken using proportional sampling technique. Data were collected once using questionnaire included: attitude, subjective norm, self efficacy and intention to be a bystander CPR. Results: Chi-square test revealed that the relationship between independent variables and intention to be a bystander CPR were: attitude p=0,00, self efficacy p=0,00 and subjective norm p=0,00. The result of multivariate analysis with logistic regression showed that: attitude p=0,004 (OR=5,279), subjective norm p=0,001 (OR=5,824) and self efficacy p=0,001 (OR=5,709). Conclusion: There were significant relationship between attitude, subjective norm and self efficacy with intention, where subjective norm was the most dominant factor associated with intention of nursing student to be a bystander CPR.